2005
DOI: 10.4049/jimmunol.174.4.2297
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Induction of Heme Oxygenase 1 in Mouse Macrophages following Melanocortin Receptor Activation

Abstract: RAW264.7 cell incubation with adrenocorticotrophin (ACTH) led to a time-dependent (4–24 h) and concentration-related (1–100 ng/ml) induction of heme oxygenase (HO)-1, and this was a specific effect, because the pattern of expression of other cellular proteins (HO-2, heat shock proteins 70 and 90) was not modified by ACTH. Combined RT-PCR and Western blot analyses revealed expression of the melanocortin receptor (MC-R) types 1 and 3, but not 4, in these cells. However, use of more selective agonists (including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 39 publications
2
44
0
Order By: Relevance
“…We have previously shown that rodent knee joint and peritoneal macrophages express MC1R and MC3R [16,22] a cell type that responded with down-regulatory events to the addition of non-selective melanocortins. The expression of MC3R on MØ membrane protrusions was confirmed by immuno-gold labelling utilising electron microscopy [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that rodent knee joint and peritoneal macrophages express MC1R and MC3R [16,22] a cell type that responded with down-regulatory events to the addition of non-selective melanocortins. The expression of MC3R on MØ membrane protrusions was confirmed by immuno-gold labelling utilising electron microscopy [14].…”
Section: Discussionmentioning
confidence: 99%
“…To date five MCRs have been identified and they are all positively coupled to adenylate cyclase, signaling via protein kinase with agonism at these receptors leading to increases in intracellular cAMP [11]. Melanocortin peptides have long been reported to possess antiinflammatory effects in many experimental models of acute [12][13][14] and chronic inflammation, including inflammatory bowel disease [15], joint arthritis [16,17] and activation and consequent cytokine synthesis within the first few hours of treatment [20,21] and at later time points (>8h) induce the anti-inflammatory protein hemeoxygenase 1 [22] and IL-10 [24]. Only one study has so far addressed the role of α-MSH in modulating eosinophil accumulation levels in a murine model of allergic airway disease [19]: α-MSH treatment of allergic mice led to a significant reduction in inflammation and this protective effect was associated with augmented IL-10 production.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Rac1 is activated by the receptor and mediates vGPCR-induced transformation in cells and tumorigenesis in animal models (28,31), whereas RhoA is required for vGPCR-induced NFB activation and interleukin-8 secretion (29). Although it is known that some GPCRs induce HO-1 expression (5,(32)(33)(34), the nature of the molecules connecting these receptors to HO-1 expression has not been established.…”
mentioning
confidence: 99%
“…Because of the antioxidant properties of the heme metabolism products, HO-1 has been considered a cytoprotector molecule involved in several physiological responses against inflammation and oxidative and cellular stress (2). However, an increasing number of studies have now expanded this notion defining HO-1 as an important regulator of the physiology of the vasculature, endothelial cell cycle control, proliferation, vascular endothelial growth factor (VEGF) 5 secretion, angiogenesis, and tumorigenesis (3, 8 -14). A recent study shows that HO-1 expression is induced in endothelial cells infected by the angiogenic and oncogenic Kaposi sarcoma-associated herpesvirus (KSHV) and that the enzyme is highly expressed in biopsy tissues from oral AIDS-Kaposi sarcoma lesions (15).…”
mentioning
confidence: 99%